Flexural behaviour of pultruded circular tubular GFRP composite truss bridges with novel non-corrosive connections. (November 2022) - Higgoda, Thumitha Mandula; Elchalakani, Mohamed; Kimiaei, Mehrdad; Wittek, Adam; Yang, Bo
Abstract: Five multiplanar truss bridges (MTBs) made of glass-fibre reinforced polymer (GFRP) circular tubular profiles incorporating different innovative non-metallic connections with adhesives, grouted GFRP rods and GFRP laminate wrapping are proposed. These MTBs were tested under flexure with static loading, and their performance surpassed the design load demands required by pedestrian bridges. One of the MTBs showed sufficient load capacity for heavy load platforms in Australian road bridge applications. Failure of the MTBs was triggered by member connections, and no damage such as local or member buckling of the individual members was observed. It was found that the combined effect of GFRP rods and GFRP wrapping on the connections increased the ultimate strength and the ductility of the MTBs. The capacity of the members and connections for the MTBs were calculated using available design guidelines and analytical equations which were compared and discussed with the experimental results.